Parliament in print: William Caxton and the history of political government in the fifteenth century - Kern, Darcy (Journal of Medieval History, 2014)
This article explores the narrative of parliamentary history in fifteenth-century England, specifically as found in the texts William Caxton printed. It investigates Caxton's approach to history and motivation for choosing texts, his translations and vocabulary, his editorial oversight and his audience. As his confidence in his own skill grew, and as he moved from a continental to an English context, his reading of parliaments changed. Initially it corresponded to his French texts, but by the early 1480s he understood the term ‘parliament’ to mean some variation of the contemporary English Parliament. Caxton's later understanding is reflected in the histories he published. This article emphasises the importance of Caxton's historical narratives to Parliament's legitimacy and to political discourse in a time when few parliaments were held.
_eprint: https://doi.org/10.1080/03044181.2014.895958
Keywords: England; William Caxton; dept.his; history; legitimacy; parliament; peer-reviewed; print

World War I and Propaganda - Paddock, Troy R. E. (Brill, 2014)
Keywords: Propaganda; World War; 1914-1918; dept.his; faculty_collection

Building within space: thoughts towards an environmental ethics - Paddock, Troy (Ethics in Progress, 2014)
The need for constructing an environmental ethics that keeps sustainability in mind is the result of a collision of the realization that the natural environment is neither limitless nor impervious to actions with a view of nature that has been fundamentally instrumentalist and anthropocentric. This paper will borrow from architectural theory in an effort to do two things: First, it will point to some of the limitations of an anthropocentric view of nature and how it impacts efforts to influence environmental policy; second, it will suggest that ideas from Aristotle and Actor Network Theory can help to provide a paradigm within which we can think about nature in a way that offers an alternative framing of questions about the environment.
0 citations (Crossref) [2023-10-31]
Keywords: dept.his

World War I and Propaganda - Paddock, Troy R. E. (Brill, 2014)
World War I and Propaganda offers a new look at a familiar subject. The contributions to this volume demonstrate that the traditional view of propaganda as top-down manipulation is no longer plausible. Drawing from a variety of sources, scholars examine the complex negotiations involved in propaganda within the British Empire, in occupied territories, in neutral nations, and how war should be conducted. Propaganda was tailored to meet local circumstances and integrated into a larger narrative in which the war was not always the most important issue. Issues centering on local politics, national identity, preservation of tradition, or hopes of a brighter future all played a role in different forms of propaganda. Contributors are Christopher Barthel, Donata Blobaum, Robert Blobaum, Mourad Djebabla, Christopher Fischer, Andrew T. Jarboe, Elli Lemonidou, David Monger, Javier Pounce,Catriona Pennell, Anne Samson, Richard Smith, Kenneth Andrew Steuer, María Inés Tato, and Lisa Todd.
Publication Title: World War I and Propaganda
Keywords: dept.his

The early qadariyya - Judd, Steven C. (The Oxford Handbook of Islamic Theology, 2014)
This article discusses the briefly significant Qadariyya movement during the Umayyad period, with an emphasis on how the movement and its adherents were treated in later sources. The article examines the doctrine of human free will advocated by the Qadariyya, exploring the impetus behind their theological viewpoints and the doctrinal complications that accompanied human free will. It also addresses the debate about the origins of both the doctrine and the movement, and the significance of accusations of Christian roots. The article discusses the views ascribed to prominent Qadari leaders, including Maʿbad al-Juhanī and Ghaylān al-Dimashqī, as well as the systematic persecution of the Qadariyya, led by al-Awzāʿī. It also examines the politicization of the Qadariyya and their entanglement with Yazīd (III) b. al-Walīd’s rebellion during the third fitna. Finally, the article addresses the eclipse of the Qadariyya by the Muʿtazilites.
Keywords: dept.his

Reimagining indian country: native american migration and identity in twentieth-century los angeles. - Amerman, Stephen (Journal of American History, 2014)
0 citations (Crossref) [2023-10-31] tex.eissn: 1945-2314 tex.unique-id: ISI:000339885600122
Keywords: dept.his; peer-reviewed

The indian school on magnolia avenue: voices and images from sherman institute - Amerman, Steve (Ethnohistory, 2014)
0 citations (Crossref) [2023-10-31] tex.eissn: 1527-5477 tex.unique-id: ISI:000331100800014
Keywords: dept.his

Religious Scholars and the Umayyads: Piety-Minded Supporters of the Marwānid Caliphate - Judd, Steven C. (Routledge, 2014)
SCSU Faculty Scholar Award
Keywords: Doctrines; History; Judges (Islamic law); History; Muslim scholars; Islamic law; SCSU Faculty Scholar Award; Umayyad dynasty; Islam; award_winner; dept.his; faculty_collection

Map worlds: A history of women in cartography. by will c. van den hoonard - Petto, Christine M (Imago Mundi, 2014)
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/027-906-651-640-986 tex.type: [object Object]
Keywords: dept.his

Book Review: Jack Johnson, rebel sojourner: boxing in the shadow of the global color line - Rondinone, Troy (International Journal of the History of Sport, 2014)
0 citations (Crossref) [2023-10-31] tex.eissn: 1743-9035 tex.unique-id: ISI:000338727900016
Keywords: book.review; dept.his